Predictors of Mental Health Among ECE Teachers: The Role of Stress, Social Support, and Resilience - Ega Asnatasia Maharani; Siti Dinni (SEA-CECCEP, 2022)
Teacher's mental health has become a major issue around the world. This is a preliminary study aimed to explore stress, social support, and resilience as potential values that can predict the mental health of early childhood education (ECE) teachers. Participants in the study included 120 ECE teachers in Yogyakarta who had a minimum of 2 years working duration. The instruments utilized for data collection were General Health Questionnaire (GHQ-12), Perceived Stress Scale (PSS-10), Multidimensional Scale of Perceived Social Support (MSPSS), and The Brief Resilience Scale (BRS). The four scales were distributed to 19 schools in the Yogyakarta area, both online and in person. The collected data were analyzed using multiple linear regression. The study indicated that stress, social support, and resilience jointly affected mental health status by 52,7% (sig .000 < .05). From the three independent variables, resilience acted as the strongest predictor with a correlation coefficient of -.703 and a relative contribution of 44.7%. This study concluded that stress management and resilience can be developed as an intervention construct to improve teachers' mental health. Further implications of the findings of this study have been discussed in the article.